The quality of life of regional and remote cancer caregivers in Australia. (11th April 2022) - Goodwin, Belinda C.; Crawford‐Williams, Fiona; Ireland, Michael; March, Sonja; Chambers, Suzanne K.; Aitken, Joanne F.; Dunn, Jeff
Abstract: Objective: This study compares the well‐being of rural caregivers with that of the general population and explores the potential drivers of poorer outcomes. Method: Patient–caregiver dyads ( n  = 241) residing in regional or remote Queensland, Australia, reported on QoL, chronic illness, caregiver burden, depression, anxiety and stress. Caregiver outcomes were compared with population norms and patient outcomes. Multiple regressions were conducted to identify factors associated with poorer caregiver outcomes. Results: Caregivers reported lower mental health‐related QoL (M = 0.436, 95% CI = 0.410–0.462) in comparison with age‐matched population norms (M = 0.556, 95% CI = 0.532–0.580). No differences existed between caregiver and population norms for anxiety, stress and depression. Caregiver chronic illness and higher burden were associated with poorer mental and physical QoL, depression, anxiety and stress ( η 2 s ranging from 0.03 to 0.30). These associations were slightly stronger for male caregivers when compared with female caregivers ( η 2 s ranging from 0.03 to 0.08). Conclusion: It is vital that efforts are made to improve rural caregivers' mental and emotional well‐being. Interventions that support caregivers with chronic conditions reduce caregiver burden and take into consideration the unique experience of male caregivers will go some way to addressing this. Future research is needed to identify other drivers of health outcomes in this group.